ANALISIS NATRIUM DIKLOFENAK PADA JAMU ASAM URAT YANG BEREDAR DIKABUPATEN HULU SUNGAI TENGAH MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Muhammad; Mi’rajunnisa; Muhammad Awaluddin Padjrin; Yulianita Pratiwi Indah Lestari; Risa Adhyani; Muhammad Muhammad (Bajang Institute, 2026)
Abstract: The government has strictly prohibited traditional medicines from containing chemical substances, whether derived from isolation or synthetic processes. Sodium diclofenac, which falls under the category of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs), is often misused in herbal preparations. This study aims to detect the presence of sodium diclofenac in illegal gout herbal products circulating in Hulu Sungai Tengah Regency using Thin Layer Chromatography (TLC), alongside UV-Vis spectrophotometry for quantitative analysis. The method has met the validation parameters (linearity, precision, accuracy, LOD, and LOQ). Qualitative analysis results idetitied that 1 of 5 herbal samples, J1, tested positive for sodium diclofenac with an Rf value of 0.64. The UV-Vis spectrophotometer method utilizing methanol as a solvent has met the validation parameters, with results showing r = 0.9998, %RSD = 0.38%, and % recovery = 100.74%. The LOD is 0.4862 ppm, and the LOQ is 1.6206 ppm. The concentration of sodium diclofenac in sample J1 is 17.7475 mg/1g (1.77%). Based on the analysis results, it is known that one of the gout herbal products circulating in Hulu Sungai Tengah Regency tests positive for sodium diclofenac. It is imperative that the BPOM conducts continuous monitoring of the circulation of herbal products in the community in order to reduce the incidence of herbal products containing BKO.